Diet and helminths of Enyalius brasiliensis (Lacertilia, Iguania, Leiosauridae) in an Atlantic Rainforest remnant in southeastern Brazil - Dorigo,TA (2014)
Our study aimed to add information about the diet and endoparasites of Enyalius brasiliensis from an Atlantic Rainforest remnant in the state of Rio de Janeiro, southeastern Brazil. Regarding diet, E. brasiliensis consumed arthropods, with caterpillars and beetles being the most important preys. Regarding helminth parasites, overall prevalence was low (9.5%), with 238 nematodes of the genus Physaloptera found in the stomach of one specimen and one nematode of the genus Rhabdias inside the lung of another. Our results corroborate the observations of previous studies that indicate that lizards of the genus Enyalius tend to feed mainly on relatively large-bodied arthropods and to harbour depauperate endoparasite fauna.